Short-term impact of combining pain neuroscience education with exercise for chronic musculoskeletal pain: a systematic review and meta-analysis. Issue 1 (9th January 2022) - Siddall, Benjamin; Ram, Adrian; Jones, Matthew D.; Booth, John; Perriman, Diana; Summers, Simon J.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Exercise and pain neuroscience education (PNE) have both been used as standalone treatments for chronic musculoskeletal pain. The evidence supporting PNE as an adjunct to exercise therapy is growing but remains unclear. The aim of this systematic review and meta-analysis was to evaluate the effect of combining PNE and exercise for patients with chronic musculoskeletal pain, when compared with exercise alone. A systematic search of electronic databases was conducted from inception to November 6, 2020. A quality effects model was used to meta-analyze outcomes where possible. Five high-quality randomized controlled studies (n = 460) were included in this review. The PEDro scale was used to assess the quality of individual studies, and Grading of Recommendations, Assessment, Development, and Evaluation analysis was conducted to determine the quality of evidence for each outcome. Meta-analyses were performed for pain intensity, disability, kinesiophobia, and pain catastrophizing using data reported between 0 and 12 weeks postintervention. Long-term outcomes (>12 weeks) were only available for 2 studies and therefore were not suitable for meta-analysis. Meta-analysis revealed a significant difference in pain (weighted mean differences, −2.09/10; 95% confidence interval [CI], −3.38 to −0.80; low certainty), disability (standardized mean difference, −0.68; 95% CI, −1.17 to −0.20; low certainty), kinesiophobia (standardized mean difference, −1.20; CI, −1.84 to −0.57; moderate certainty), and pain catastrophizing (weighted mean differences, −7.72; 95% CI, −12.26 to −3.18; very low certainty) that favoured the combination of PNE and exercise. These findings suggest that combining PNE and exercise in the management of chronic musculoskeletal pain results in greater short-term improvements in pain, disability, kinesiophobia, and pain catastrophizing relative to exercise alone.